EFFECT OF BOKASI MADE FROM NARROW LEAF WEED TO GROWTH AND YIELD OF CHINASE KALE CULTIVATED ON ALLUVIAL SOIL - ersandi sandi; - Warganda; evi gusmayanti (Jurnal Sains Pertanian Equator, 2017)
The research was aimed to analyze the effect of bokashi made from narrow leaf weed on growth and yield of chinase kale on cultivated alluvial soil. The research was conducted at experimental farm of agriculture, faculty UniversityTanjungpura Pontianak. From December 2016 to February 2017. The researchwas arranged according to completely randomized design (CRD), there were 6treatments, of 4 replications with 3 samples each. The treatments were p0 (0 gbokashi/polybag), p1 (180 g bokashi/polybag, equivalent to 9 ton/ha), p2 (360 g bokashi/polybag, equivalent to 18 ton/ha), p3 (540 g bokashi/polybag, equivalent to 27 ton/ha), p4 (720 g bokashi/polybag, equivalent to 36 ton/ha), and p5 (900 g bokashi/polybag, equivalent to 45 ton/ha). Variables observed in this study were root volume (cm3), chlorophyll content (spad unit), plant height (cm), leaf area (cm2), and fresh weight (g). The results show that application of bokashi increase growth and yield of chinase kale. The dose of 900 g/polybag bokasi or equivalent to 45 tons / ha seemed to be relatively better the other dosesKey words : alluvial, chinase kale, narrow leaf weeds